Urban park and geoconservation: the case of BicãoPark, São Carlos – São Paulo, Brazil - Toyama, Daniele; Mendonça, Irene da Rocha; Capoia, Emilene Frazão; Fagundes, Julia Guenka; Menezes, Denise Balestrero (Sociedade & Natureza, 2018)
This paper emphasizes on the relevance of the urban geosites towards the valorization of the public areas. It also presents a set of data regarding the physical and environmental aspects of Bicão Park, located in the city of São Carlos -SP, obtained through photos, thematicmaps, actual visits to the site and reports given by those who attend to this place and also by those who live nearby. The place is home for several unique characteristics, resulting in a potential area for the implementation of an urban geopark. It is one of the few remaining green areas in the city portion which the population is aware of its importance, hence, being indispensable some actions that seek to improve this environment. The transformation of the area into a geosite would imply in the appreciation of the area by the community, strengthening the bonds between the man and the site where he dwells. Besides that, the possibility of doing environmental sensitizing activities is an essential tool to universalize the knowledge of the geosciences.